PRELIMINARY RESULTS OF ELECTROPHORETIC STUDIES ON MARINE PRAWNS - Thomas, M M (Indian Journal of Fisheries, 2011)
Electrophoretic separation of tissue proteins of fish and prawns has been generally acclaimed as a promising technique for the detection of population units (Johnson et al 1974). This technique has been found useful in answering questions on systematics or population genetics in penaeid prawns of the Gulf of Mexico (Lester 1979).